Fuyuan Xingnao Decoction Promotes Angiogenesis Through the Rab1/AT1R Pathway in Diabetes Mellitus Complicated With Cerebral Infarction - Deng, Dong; Qu, Yao; Sun, Lihua; Jia, Liyang; Bu, Jianhong; Ye, Miaoqing; Chen, Zhenyi; Geng, Yun; Zhou, Shuang; Fang, Bangjiang (Frontiers in Pharmacology, 2021)
Fuyuan Xingnao decoction (FYXN), a traditional Chinese medicine comprised of seven herbs, has been utilized to treat diabetes mellitus complicated with cerebral infarction (DMCI) for years. Yet its protective and regulatory mechanism is poorly understood.Aim of the study is to investigate the effects of FYXN on DMCI in vitro and in vivo, as well as its angiogenesis mechanism. For in vivo experiments, FYXN was administered to DMCI rats with streptozotocin (STZ) injection-induced diabetes. Then middle cerebral artery occlusion (MCAO) was conducted and the cerebral cortex sections of the rats were obtained. The ultrastructure of cerebral microvessels and new vessel density of ischemic penumbra were evaluated by the transmission electron microscopy (TEM) assay and immunohistochemistry, respectively. Protein and mRNA expression levels of Rab1/AT1R in cortex were assayed by Western blotting and real-time fluorescence quantitative real-time polymerase chain reaction (RT-qPCR) technique. In vitro, FYXN serum was produced in rats on the fourth day 2 h after the last FYXN administration. Green fluorescence was observed after transfection with lentivirus packaged Rab1-WT or siRNA for 24 h. The activity of brain microvascular endothelial cells (BMECs) treated with sera from these rats was tested by MTT assay and Transwell assays, respectively. The expression of AT1R on the cell membrane and endoplasmic reticulum of the BMECs was evaluated by immunofluorescence staining. Protein expression levels of signaling molecules in the Rab1/AT1R pathways were also detected. Mechanistically, results showed that in vivo, FYXN treatment significantly increased CD31 staining in the cortical areas and enhanced the expression level of AT1R, Ang II, Rab1a, Rab1b and VEGF mRNA and protein in ischemic cerebral cortex tissues. In vitro, the expression levels of AT1R, Ang Ⅱ, Rab1a, Rab1b and VEGF in the cerebral infarction model group were significantly higher than those in the control group, and further increased after administration of FYXN drug serum. FYXN promoted proliferation and migration of BMECs by activating the Rab1/AT1R signaling pathway. In Conclusion, FYXN exerts a protective effect against DMCI by promoting angiogenesis via the Rab1/AT1R pathway, which provides strong evidence for the therapeutic effect of FYXN on DMCI.